The effective implentation of Performance Management and Development System in the Public Service : a case study of the Department of Public Works, Roads and Transport at Ehlanzeni District Municpality in Mpumanlanga Province - Nyoni, Ntombifuthi Eunice (My University, 2018)
Thank you to the Most High God for giving me strength, courage, wisdom and understanding to pursue my dream. Compiling this mini-dissertation would not have become a success if it was not for the support I received from my family and close friends. I would like to extend my sincere gratitude to the following persons who contributed immensely to the undertaking of this study from its beginning to its completion:  My Supervisor, Dr. K.S. Milondzo and my Co-Supervisor, Professor. M.X Lethoko for their constructive criticism, patience, expert advice and motivation and for being the sound board of my ideas throughout the process. For the professionalism that they portrayed throughout our interaction.  To Professor C.S. Mkhabela for his academic advice, moral support and fruitful discussions we had in our engagement.  My parents Pauline and Ben Nyoni, for their undivided support, patience, and acceptance.  My son, Tshepo Litswele for his unwavering love and support  My brothers and sisters, for their support, tolerance and acceptance at times I may have inconvenienced them.  To the participants for willingness to participate in the study.  To my employer Department of Education for allowing me to pursue my studies.  To the Department of Public works, Roads and Transport for granting me permission to conduct my research within their department.  To Ms MM Ngobeni for her professional editing. iv ABSTRACT Recent changes in the public sector which also included the Department of Public Works, Roads and Transport have placed new pressure on managers to change their ways of managing Performance Management and Development Systems in its implementation. The above challenge necessitated the researcher to investigate the effective implementation of Performance Management System in the Department of Public Works, Roads and Transport in Ehlanzeni District Municipality. The study is concerned with the development of effective implementation of Performance Management System on employees and production in the Department of Public Works, Roads and Transport. This study used the context of the Department of Public Works, Roads and Transport as its spring board in engaging the subject of performance management system. With all changes that are involved towards the implementation of performance management system, there is a need to review the way performance management system should be implemented, hence this study. In this study, a mixed research design approach was used in the investigation of the effective implementation of performance management system in the Department of Public Works, Roads and Transport. Questionnaires and semi-structured interviews were employed to collect data from the target population. The main findings of the study, confirmed that there are challenges associated with the implementation of performance management system in the Department of Public Works, Roads and Transport. Apart from these challenges, the study also revealed the factors that contribute towards the implementation of performance management system in the area of the study. Furthermore, the study also led to the suggestions and recommendations that may assist Ehlanzeni District Municipality to accelerate effective implementation of performance management system in the department.
Thesis (M. Dev.) -- University of Limpopo, 2018
Keywords: Performance management; Performance management system; Department of Public Works, Roads and Transport; Performance - Management.; Performance standards; Employees rating of